THE ARMENIAN IMMIGRATION TO EGYPT IN THE 19TH CENTURY - Ahmed, Yehia Mohamed Mahmoud (European Scientific Journal, ESJ, 2014)
Egypt has witnessed several waves of Armenian immigration through history particularly during the Ottoman era in Egypt and Arab world from the sixteenth century until the nineteenth century. After years of settlement and immigration, the Armenian minority became part and parcel of the multi-ethic/multi-cultural Egyptian society. Due to their commitment and dedication, the Armenians gained a reputation as experts in the fields of business and commerce244. This paper investigates the effect of this immigration on Egypt in the 19th century and the participation of the Armenian people in Mohamed Aly’s civilizational project which put Egypt on the map of the modern world. The paper will explore the significant role, played by Boghos Yosefyan, the central political and economic advisor of Mohamed Ali, in the development of the Egypt Renaissance. Based on the mutual correspondences (and letters) between the two parties (Mohamed Ali and Boghos) in addition to other historical documents, pursued in the Egyptian historical Archive, this study traces the nature of the role played by Boghoss Yosefyan in the construction of the Egyptian Renaissance during the first half of the nineteenth- century.